Efficacy of ICT-Based Neurocognitive Rehabilitation Programs for Acquired Brain Injury - Geraldo, Andreia (2019)
This systematic review aims to analyze the methods used in the assessment of the efficacy of Neurocognitive Rehabilitation Programs (NRP) based on Information and Communication Technologies in patients with Acquired Brain Injury, namely platforms and online rehabilitation programs. Studies with the main purpose of evaluating the efficacy of those programs were retrieved from multiple literature databases, accordingly to inclusion and exclusion criteria. The inclusion and analysis of the studies followed preferred reporting items for systematic review and meta-analysis protocols (PRISMA-P) and Cochrane Collaboration Guidelines. Thirty-one studies were included in this review. Results showed that most studies used a pre-post methodological design, with few studies performing assessment moments during intervention or follow-up. Attention, memory, and executive functions were the cognitive variables considered by a larger number of studies at the assessment of NRP efficacy. Despite that, there is a growing evidence on the inclusion of variables related to everyday functioning in this process, increasing its ecological validity. Concerning the instruments used, the studies presented a large heterogeneity of the instruments and methods used, even for the same assessment purpose, highlighting a lack of consensus regarding assessment protocol. Psychophysiological and neuroimaging techniques are seldom used on this field. This review identifies the main characteristics of the methodology used at the assessment of NRP and potential limitations, providing useful information to guide the practice of the health care professionals in rehabilitation of Acquired Brain Injury. It also suggests new directions for future studies